Therapeutic advantages of the combined use of closantel and moxidectin in lambs parasitized with resistant gastrointestinal nematodes - Suárez, Gonzalo (2023)
The serious widespread development of nematode resistance has motivated the use of combined anthelmintic formulations. However, the advantages/disadvantages of the combined use of anthelmintics require further scientific characterization. The goals of the current trial were a) to characterize the pharmacokinetics of closantel (CLO) and moxidectin (MXD) administered both subcutaneously (sc) and orally either separately or co-administered (CLO + MXD) to lambs; b) to compare the nematodicidal activity of both molecules given individually or co-administered to lambs infected with resistant nematodes. Seventy (70) Corriedale lambs naturally infected with multiple resistant gastrointestinal nematodes were involved in the pharmacokinetic and efficacy trials. The animals were allocated into six groups (n = 10) and treated with either CLO, MXD, or with the CLO + MXD combined formulation by both the oral and sc routes. Additionally, an untreated control group (n = 10) was included for the efficacy trial. The efficacy was estimated by the faecal egg count reduction test (FECRT). Higher systemic exposure of both CLO and MXD was observed after the sc compared to the oral administration in lambs. The combined administration of CLO + MXD did not markedly alter their disposition kinetics. At 13 days post-treatment, the administration of both molecules as a single active principle reached efficacy levels ranging between 80% (MXDoral), 84% (CLOoral), 85% (CLOsc), and 92% (MXDsc). The combined oral and sc treatments reached 99% efficacy. No adverse effects were observed after the combined treatment of CLO + MXD, and their co-administration did not show any adverse pharmacokinetic interaction. The combined effect of CLO + MXD successfully restored the maximum efficacy levels, which were not reached by the individual active ingredients.